Esperienza della fatticità e Kairós nella Vorlesung heideggeriana del 1920/21 - Colonnello, Pio (Bollettino Filosofico, 2020)
In the Vorlesung Einleitung in die Phänomenologie der Religion of 1920/21, Heidegger, following some Pauline suggestions deriving from the Letters to the Corinthians and Thessalonians, resorts to a conception of time as a “setback”, that is, as a countermovement that dissolves the “vulgar conception of time”, thereby revealing itself as a “time in reverse”. This time has to be understood as the Kairós, from which all moments of life acquire meaning. The presence of the proto-Christian experience and the Letters of St. Paul is thus crucial not only for a general understanding of the speculative horizon in which Heidegger’s hermeneutics is placed, but also for the very position of the question about the historicity of existence and the irruption of Kairological time into actual life. This perspective allows room for a redefinition of the meaning of being, which can no longer be taken as “mere presence”, nor as “ousiai”, but should rather be understood as “Parousia”. Keywords: Eigentlichkeit, Factice Life, Kairós, Parousia